SCIENCE MUSEUMS AND FORMATION OF SCIENTIFIC COLLECTIONS:: FROM ALEXANDRIA TO THE 19TH CENTURY (Interdisciplinary Studies Journal, 2025)
The Alexandria Complex (180 BC) is considered the first documented museum site, where there was the "Mouseion", a space dedicated to the exhibition of pieces and the exchange of knowledge. Thus, over time, museums and collections underwent significant transformations, with emphasis on the 18th century, when the Enlightenment boosted the development of knowledge, science museums and scientific collections, which began to have a public and educational character. In the 19th century, profound changes occurred worldwide, and museums organized themselves, diversifying their collections, reflecting advances in science and technology. Collections such as fossils and ethnographic artifacts illustrated the progress of natural sciences and technology. Science and Natural History Museums began to be seen as important instruments in the dissemination of scientific knowledge, contributing to the popularization of science and cultural development. This work, focusing on the period between 180 BC and the 19th century, explores the evolutionary milestones of museums, highlighting how scientific museums emerged from cabinets of curiosities and transformed into encyclopedic museums. These institutions accumulated collections that were not only scientific, but also curious and fantastic, exhibiting them in an organized and systematic way, valuing theories, rarity and grandeur of the pieces.
Keywords: Museums; Science Museums; Scientific Collections